1851 Terr. of Minn. Rev. Stat. 528 - (:unkn) unknown (My University, 1851)
Ch. 112, § 18: Required any person going armed with any dirk, dagger, sword, pistol, or other offensive and dangerous weapon to post a surety once a complaint was filed, having cause to fear an injury or breach of the peace. Surety not to exceed six months with appeals provided. §18 provided that a surety may surrender his principal upon breach of the condition of recognizance.
Keywords: SURETY